Abortion Stigma: A Systematic Review. Issue 4 (31st March 2016) - Hanschmidt, Franz; Linde, Katja; Hilbert, Anja; Riedel‐ Heller, Steffi G.; Kersting, Anette
Abstract : Context: Although stigma has been identified as a potential risk factor for the well‐being of women who have had abortions, little attention has been paid to the study of abortion‐related stigma. Methods: A systematic search of the databases Medline, PsycArticles, PsycInfo, PubMed and Web of Science was conducted; the search terms were "(abortion OR pregnancy termination) AND stigma * ." Articles were eligible for inclusion if the main research question addressed experiences of individuals subjected to abortion stigma, public attitudes that stigmatize women who have had abortions or interventions aimed at managing abortion stigma. To provide a comprehensive overview of this issue, any study published by February 2015 was considered. The search was restricted to English‐ and German‐language studies. Results: Seven quantitative and seven qualitative studies were eligible for inclusion. All but two dated from 2009 or later; the earliest was from 1984. Studies were based mainly on U.S. samples; some included participants from Ghana, Great Britain, Mexico, Nigeria, Pakistan, Peru and Zambia. The majority of studies showed that women who have had abortions experience fear of social judgment, self‐judgment and a need for secrecy. Secrecy was associated with increased psychological distress and social isolation. Some studies found stigmatizing attitudes in the public. Stigma appeared to be salient in abortion providers' lives. Evidence of interventions to reduce abortion stigma was scarce. Most studies had limitations regarding generalizability and validity. Conclusion: More research, using validated measures, is needed to enhance understanding of abortion stigma and thereby reduce its impact on affected individuals.